Developing Ecotourism and its Supporting MSMs Using Performance, Opportunity and Results Analysis. Case Study in Pekalongan Regency, Indonesia - SUSILOWATI, MG Westri Kekalih; WAHYUNINGDYAH, Retno Yustini; KURNIASARI, Widuri (Journal of Environmental Management and Tourism, 2020)
The development of the tourism sector and its supporting MSMEs have a positive impact on the society. However, various classic problems of MSME cause the MSME’s competitiveness be relatively low and have not been able to provide optimal benefits for the community. Efforts to empower MSMEs and tourism are important to do. Empowerment policy must be comprehensive. Therefore, general policy directions, strategies and priority issues have to be formulated to suit the conditions and needs to achieve the goal. Using an Importance-Performance Analysis (IPA) approach combined with a Strength, Opportunity analysis Aspiration and Result (SOAR) analysis approach, this study aimed to formulate general policy directions and strategies and to highlight the priority of the issues. The study, conducted in Pekalongan Regency, Indonesia. There were 60 participants that come from local governments, academics, and community leaders as respondents. The results show that promotion and price mix are considered relatively high importance-low performance. Meanwhile, SOAR analysis shows that the endowment factors, the motivation of MSME’s actors and government policies are their strength. Thus, in the short term, it is necessary to increase price and promotion performances to improve the quality of tourism MSMs. In the long term, it is necessary to strengthen institutions and improve the quality of human resources.